Use of an additive canthaxanthin based and annatto extract in diets of laying hens and its effect on the color of the yolk and the egg shelf life - Rojas, Víctor (2015)
The aim of this study was to evaluate the use of an additive canthaxanthin based and annatto extract (Bixa orellana L.) in diets of laying hens and its effect on the color of the yolk and the egg shelf life. Position 864 hens 34 to 45 weeks old, distributed in a completely randomized design with six replicates per treatment were used. Treatments were T0 (control diet), T1 (T0 + 30 g of canthaxanthin and annatto extract) and T2 (T0 + 60 g of canthaxanthin and annatto extract). The results were 88.6; 91.9 and 90.8% for laying percentage; 60.5; 61.6 and 61.5 g for egg weight; 53.6; 56.4 and 55.7 g for egg mass. The yolk color temperature 7 °C for Roche scale was 6, 9 and 12 and colorimetric Minolta was to "L" of 42.10; 40.24 and 39.65; for "a" of 0.07; 3.68 and 6.44 and for "b" of 19.35; 18.36 and 18.18. Shelf life at room temperature 7 °C was 81, 86 and 90 UH. Lipid peroxidation was 0.10; 0.07 and 0.05 µmol MDA.g-1 yolk; for T0, T1 and T2 respectively. In all variables indicated statistically significant differences between treatments (p < 0.05). Food consumption was 103.9; 109.2 and 107.5 g and feed conversion of 1.94; 1.93 and 1.92. It is concluded that the addition of canthaxanthin and annatto extract to 30 and 60 g t-1 feed than the control, improved performance parameters, yolk color and egg shelf life.